Akhlak Peserta Didik Perspektif Al Ghazali dan Quraish Shihab (Studi Kitab Ayyuhal Walad dan Buku yang Hilang dari Kita “Akhlak”) - Muh Ainul Fiqih; Muh. Fajar Shodiq (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Morals are an important part of Islam and education. Seeing the many cases of students committing immorality, promiscuity, and drugs makes it important to discuss the morals of students. The objectives of this study are 1) Knowing the morals of students according to Al Ghazali in the book Ayyuhal Walad. 2) Knowing the morals of students according to Quraish Shihab in the book Missing From Us: Morals. The type of research used is library research using the documentation method with complex and thorough data validity checking techniques. The data obtained were analyzed using content analysis techniques. The results of the study are: 1) Al Ghazali mentions several morals for students which lead to a clean-spirited human process that is close to God. Like, obedience to Allah, piety, trust, fond of reading, choosing a teacher, praying. 2) Quraish Shihab is more directed at humans who are seen as virtuous creatures, namely, sincerity, mercy, reading, patience, ash shidq, tolerance, discipline.